2020
DOI: 10.1096/fj.201902692r
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin alleviates cardiac fibrosis via inhibiting lncRNA MALAT1/miR‐141‐mediated NLRP3 inflammasome and TGF‐β1/Smads signaling in diabetic cardiomyopathy

Abstract: Melatonin is a hormone produced by the pineal gland, and it has extensive beneficial effects on various tissue and organs; however, whether melatonin has any effect on cardiac fibrosis in the pathogenesis of diabetic cardiomyopathy (DCM) is still unknown. Herein, we found that melatonin administration significantly ameliorated cardiac dysfunction and reduced collagen production by inhibiting TGF‐β1/Smads signaling and NLRP3 inflammasome activation, as manifested by downregulating the expression of TGF‐β1, p‐Sm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
70
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 118 publications
(75 citation statements)
references
References 59 publications
(120 reference statements)
5
70
0
Order By: Relevance
“…In the field of cardiovascular effects, melatonin protects against ischemia/reperfusion injury (IRI) [ 62 , 117 , 118 , 119 , 120 , 121 ] and hypertension [ 122 , 123 , 124 ], as an endogenous effect, nutritional supplement, or acute parenteral administration [ 125 , 126 ]. In addition, it appears that other promising effects such as anti-apoptotic, anti-inflammatory [ 127 ], preconditioning [ 118 , 128 ], myocardial infarction [ 129 , 130 , 131 ], and even an implication in heart failure [ 132 , 133 , 134 , 135 ] have been documented. However, it seems than in some conditions, melatonin can have deleterious effects, as exaggerated collagen and glycosaminoglycans deposition and increased size in post-myocardial infarction scar have also been reported [ 136 , 137 ].…”
Section: Melatonin’s Role In Programming Adult Cardiovascular Homementioning
confidence: 99%
See 1 more Smart Citation
“…In the field of cardiovascular effects, melatonin protects against ischemia/reperfusion injury (IRI) [ 62 , 117 , 118 , 119 , 120 , 121 ] and hypertension [ 122 , 123 , 124 ], as an endogenous effect, nutritional supplement, or acute parenteral administration [ 125 , 126 ]. In addition, it appears that other promising effects such as anti-apoptotic, anti-inflammatory [ 127 ], preconditioning [ 118 , 128 ], myocardial infarction [ 129 , 130 , 131 ], and even an implication in heart failure [ 132 , 133 , 134 , 135 ] have been documented. However, it seems than in some conditions, melatonin can have deleterious effects, as exaggerated collagen and glycosaminoglycans deposition and increased size in post-myocardial infarction scar have also been reported [ 136 , 137 ].…”
Section: Melatonin’s Role In Programming Adult Cardiovascular Homementioning
confidence: 99%
“…Some studies showed that melatonin produces a decrease in the myocardial scar, reduced fibrosis [ 134 ], and remodeling after myocardial infarction [ 130 ]. In the MARIA (Melatonin Adjunct in the acute myocaRdial Infarction treated with Angioplasty) study on reperfused STEMI patients, melatonin reduces infarct size 40% if administered in the first 2.5 h after symptom onset [ 125 , 129 ].…”
Section: Melatonin’s Role In Programming Adult Cardiovascular Homementioning
confidence: 99%
“…1 DM is associated with severe damage to multiple organ systems, such as the heart, eyes, and kidneys. [2][3][4] Recently, increasing attention has been paid to the pathological changes in the brain induced by DM. Diabetes-induced brain injury manifests as neurodegeneration, cerebral infarction, and progressive cognitive decline.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies found numerous lncRNAs through microarray and RNA-seq that are crucial for the development of various diseases, especially malignant tumors 30 - 32 . According to the NCBI database, MEG3 is located on chromosome 14q32.3 in Homo sapiens and functions as a tumor suppressor in many cancers 33 , 34 .…”
Section: Discussionmentioning
confidence: 99%